‘STELLER’ AS DIGITAL STORYTELLING APP: COLLEGE STUDENTS’ PERCEPTIONS IN EFL WRITING CLASSROOMS - Arya Wiranda; Utami Dewi (The Journal of English Literacy Education: The Teaching and Learning of English as A Foreign Language, 2025)
The integration of digital storytelling in EFL writing instruction has been widely explored due to its potential to enhance student engagement and writing proficiency. This study investigates students’ perceptions of using Steller, a multimedia storytelling application, in EFL writing classrooms. The study used a qualitative case study approach, while the data were collected from fourth-year university students in Medan through questionnaires and in-depth interviews. Thirty students responded to the questionnaires, and six students were selected to follow in-depth interviews. Questionnaire data were analysed descriptively, while interview data underwent thematic analysis. The findings indicate that most students found the benefit of Steller in organizing their writing clearly, integrating multimedia, developing creativity, facilitating easier editing through drag-and-drop features, providing various writing formats, and improving collaboration. However, challenges such as internet dependency and the complexity of some features were identified as obstacles to usability. While some findings highlight the advantages of Steller in EFL writing instruction, they also suggest the need for improvements in accessibility and ease of use. This study contributes to the growing body of research on DST in language learning by providing insights into how Steller can support students in the writing process.